May Sinclair's The Three Sisters as an Early Example of Modernist Fiction - María Francisca Llantada Díaz (Miscelánea: A Journal of English and American Studies)
This paper analyses May Sinclair's novel The Three Sisters as an early example of the transition from the classic realist text to modernist fiction in English literature. The Three Sisters is here characterized as a lyrical and psychological novel, influenced by Imagism and structured around epiphanical moments, images and symbols. In addition, Sinclair's first psychological novel is considered here in the light of some of the formal and thematic principles and of the prototypes of female heroine that she was to use in her later more fully modernist novels. Thus, her later novels Mary Olivier and Harriett Frean can be understood as variations of The Three Sisters, where the representation of the unconscious feelings of the characters points to Sinclair's deep knowledge of psychoanalysis and the relevance of internal reality, a typical modernist trait.